Collaboration Skills in Seventh Grade English Textbooks: An Analysis Using the Cambridge Life Competencies Framework - Tary Arshabilla; Nurkhamidah, Neni (PRIMACY Journal of English Education and Literacy, 2024)
This study aims to determine the integration of collaboration skills in the seventh grade English textbook "English for Nusantara," published by the Indonesian Ministry of Education and Culture, using the Cambridge Life Competency Framework. Through qualitative content analysis, the research assesses the textbook's integration of skills such as active contribution, role-taking, respectful listening, mutual support, and organizational abilities. Each lesson unit was meticulously examined and coded according to the Cambridge Framework. Findings reveal a varied distribution of collaboration skills across chapters, reflecting alignment with the Merdeka Belajar Curriculum. The study concludes that the textbook effectively embeds these collaboration skills, preparing students for teamwork, task management, and collective problem-solving, thus promoting essential 21st-century competencies. These skills are crucial for students' future academic and professional success. The research highlights the importance of well-structured educational materials in developing collaborative abilities. This strategic approach ensures students are equipped with the necessary tools to thrive in a collaborative environment.